Contraceptive preferences and unmet need for contraception in midlife women: where are the data? - Siobán D. Harlow; Jennifer R. Dusendang; Michelle M. Hood; Nancy Fugate Woods (BMC, 2017)
Abstract This commentary discusses the limited availability of information on contraceptive preferences and unmet need for contraception among midlife women in both high and low income countries. Given that risk of pregnancy continues until women reach menopause and given the increased risk of pregnancy complications, elective abortion, and maternal mortality in women aged 45 to 54 years old, increased focus on gathering basic data on midlife women's preferences and unmet need is warranted.